Childhood Trauma and Somatic Complaints in Male Child Laborers and Mainstream School Children: A Comparative Study - Khan, Imran; Nadeem, Arif; Anjum, Fayyaz Ahmed (Pakistan Journal of Applied Psychology (PJAP), 2024)
The present study intended to investigate the relationship between childhood trauma and somatic complaints in male child laborers and to compare child laborers and mainstream children concerning childhood trauma and somatic complaints. In the current correlational study, a sample of 400 boys (child laborers=200; mainstream school children=200) in the age range of 6-16 years (M=12.03; SD=2.03) was selected using the multistage sampling technique from two cities i.e., Faisalabad and Chiniot of Punjab province, Pakistan. The Childhood Trauma Questionnaire-Short Form (Bernstein, et al., 1994) and Somatic Complaints List (Jellesma et al., 2007) were used in the Urdu language to assess childhood trauma and somatic complaints respectively. Pearson product-moment correlation, regression analysis, and t-test through Statistical Package for Social Sciences (SPSS v-25) were conducted for data analysis. The results indicated a significant positive correlation between childhood trauma and somatic complaints. Furthermore, childhood trauma was found to be a significant predictor of somatic complaints. Additionally, Child laborers scored significantly higher than mainstream school children on the Childhood Trauma Questionnaire and Somatic Complaints. As far as subscales of the Childhood Trauma Questionnaire are concerned, child laborers scored higher on Abuse, and Physical Neglect as compared to mainstream school children whereas, Emotional Neglect and Denial were found to be more in mainstream school children as compared to the child laborers.